Speak and Shine: “Talk Dice Game” for Young English Learners - Nussy, Wenssy Steva; Tiven, Punggulina Andawaty; Suryaningrum, Sumarah; Oraile, Orpa Penina; Ngosiem, Maria Jomima; Lorang, Liviya Donice (Civiliza Publishing, 2025)
The aim of this community service project is to investigate the implementation of the